Pertumbuhan Tithonia diversifolia dengan Dosis Pupuk Kandang dan Jarak Tanam yang Berbeda - Desyrakhmawati, Lia; Melati, Maya; ,, Suwarto; Hartatik, Wiwik (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
Mexican sunflower (Tithonia diversifolia) is a invansive weed but it can be used as continuous and on-farm source of nutrient for organic farming system. The objective of this study was to investigate growth and biomass production of T. diversifolia with different rates of chicken manure and plant spacings. The experiment was conducted at Cikarawang, Bogor, on Inceptisol soil type, from October 2011 until January 2012. The experiment was arranged in a randomized block design with 2 factors and 3 replications. The rates of chicken manure were  0, 2.5, 5 and 10 ton ha-1, while the plant spacings were 50 cm x 50 cm and 75 cm x 75 cm. The interaction effect between manure rates and plant spacing was significant on nett assimilation rate at 4-8 weeks after planting, but it was not significant on biomass production. The highest dry weight of biomass (1,129.1 kg ha-1) was obtained from the addition of 10 ton chicken manure ha-1 with the potential contribution as much as 55.47 kg N, 4.54 kg P, 88.54 kg K per hectare. The highest dry weight of biomass produced with planting distance 50 cm x 50 cm (897 kg ha-1). Referring to the results, it can be recommended that the cultivation of T. diversifolia at the first planting needs 10 ton chicken manure ha-1 and the planting distance of 50 cm x 50 cm.Keywords: biomass production, Mexican sun flower, nett assimilation ratio, nutrient contributio, weed